Frontispiece: Validating Eaton's Hypothesis: Cubane as a Benzene Bioisostere. Issue 11 (29th February 2016) - Chalmers, Benjamin A.; Xing, Hui; Houston, Sevan; Clark, Charlotte; Ghassabian, Sussan; Kuo, Andy; Cao, Benjamin; Reitsma, Andrea; Murray, Cody‐Ellen P.; Stok, Jeanette E.; Boyle, Glen M.; Pierce, Carly J.; et al.
Abstract : Bioisosteres In their Communication onpage 3580 ff., C. M. Williams, G. P. Savage, J. Tsanaktsidis et al. confirm that cubane can act as a benzene bioisostere by synthesizing and evaluating cubane derivatives of five biologically important molecules.